Encouraging Consumers to Make Online Purchases Using Mobile Applications, How to Keep them in Touch with E-Services Providers? - Zamil, Ahmad; Abu-AlSondos, Ibrahim A.; Salameh, Anas A. (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Progress in wireless technology has raised the number of people using mobile devices and stimulated the accelerated evolution of online shopping carried with these devices. However, today many corporations are making significant investments to take benefit of the new business opportunities given by internet technology, research on m-online shopping proposes potential customers may or may notadopt mobile shopping despite of their availability and benefits. Thus, this study identifies the key factors that influence customer intention to make online mobile shopping. This research investigates the dimensions of mobile shopping service based on online shoppers’ expectations and perceptions. This research developed a conceptual framework for examining the role of the perceived usefulness, perceived ease of use and trust in order to determining customers’ intention to use mobile shopping. Data were obtained from 212 students of business administration college, who conducted a mobile online shopping process, the sample was tested on the analysis model using (SEM-PLS). The results strongly support the proposed model in predicting consumer intention to use mobile shopping. the major findings of this study found positive relationship among perceived usefulness, perceived ease of use and trust association with intention to use m-online shopping. The current study model and its findings could present a rigorous basis for understanding customers’ attitude for mobile shopping contexts.